2017
DOI: 10.1107/s2052252517014658
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical effect in molecular crystals: the role of halogen-bonding interactions

Abstract: The design and synthesis of mechanically responsive materials is interesting because they are potential candidates to convert thermal energy into mechanical work. Reported in this paper are thermosalient effects in a series of halogen derivatives of salinazids. The chloro derivative, with higher electronegativity and a weaker inter-halogen bond strength (ClÁ Á ÁCl) exhibits an excellent thermal response, whereas the response is weaker in the iodo derivative with stronger IÁ Á ÁI halogen bonding. 3,5-Dichlorosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Overall, the densities were found to decrease after photoreaction (14.7% for 1 to 4, 15.6% for 2 to 5 and 12.2% for 3 to 6) and these correspond to the increase in unit cell volumes of 15.4, 17.5 and 13.1% on going from 1-3 to 4-6, respectively ( Table S2). The mobility of dynamic single crystals is usually triggered by the sudden release of stress in the form of a very fast phase transition or a chemical reaction accompanied a rapid structural change that drives these phenomena (Nath et al, 2014;Chizhik et al, 2018;Ghosh et al, 2015;Sahoo et al, 2014Sahoo et al, , 2013aSkoko et al, 2010;Rawat et al, 2018;Panda et al, 2015Panda et al, , 2016Boldyreva, 1994;Mittapalli et al, 2017). Here, the stress created by the phase heterometry due to the difference in the unit cell volumes and the release of that stress manifests as motion or explosive fragmentation of the crystals.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the densities were found to decrease after photoreaction (14.7% for 1 to 4, 15.6% for 2 to 5 and 12.2% for 3 to 6) and these correspond to the increase in unit cell volumes of 15.4, 17.5 and 13.1% on going from 1-3 to 4-6, respectively ( Table S2). The mobility of dynamic single crystals is usually triggered by the sudden release of stress in the form of a very fast phase transition or a chemical reaction accompanied a rapid structural change that drives these phenomena (Nath et al, 2014;Chizhik et al, 2018;Ghosh et al, 2015;Sahoo et al, 2014Sahoo et al, , 2013aSkoko et al, 2010;Rawat et al, 2018;Panda et al, 2015Panda et al, , 2016Boldyreva, 1994;Mittapalli et al, 2017). Here, the stress created by the phase heterometry due to the difference in the unit cell volumes and the release of that stress manifests as motion or explosive fragmentation of the crystals.…”
Section: Resultsmentioning
confidence: 99%
“…The effect was first noted in 1983, and after a long hiatus, it was explored in greater detail in the anticholinergic agent oxitropium bromide in 2010 . Encouraged by these studies, over 20 new examples have been reported in the last decade that are categorized in three classes based on their structures, with a number of notable reports of serendipitous observations increasing in the past several years . It has also been demonstrated that the rates of the TS phase transitions are several orders of magnitude faster than other, more common solid–solid transitions .…”
Section: Introductionmentioning
confidence: 99%
“…31 Recently, Mittapalli et al reported halogen-substituted Nsalicylideneaniline derivatives with a thermosalient effect. 32,33 Among the five compounds reported in their paper, one compound exhibited a thermosalient effect with a change of space group, unlike the existing compounds showing a thermosalient effect. Form Ⅰ of this compound, which was crystallised in the monoclinic space group P2 1 /c, changed into form Ⅱ, which belonged to the triclinic space group P1 � , with cracking upon heating.…”
mentioning
confidence: 97%
“…This is a rare example of the reported thermosalient effect because this effect has been generally considered to originate from a significant anisotropic lattice change without any changes in crystal system and space group. 32 During our polymorph hunting on a N,N′-bispropylated diketopyrrolo dye [3,6-…”
mentioning
confidence: 99%